2014
DOI: 10.1098/rspb.2014.1163
|View full text |Cite
|
Sign up to set email alerts
|

Matching the supply of bacterial nutrients to the nutritional demand of the animal host

Abstract: Various animals derive nutrients from symbiotic microorganisms with muchreduced genomes, but it is unknown whether, and how, the supply of these nutrients is regulated. Here, we demonstrate that the production of essential amino acids (EAAs) by the bacterium Buchnera aphidicola in the pea aphid Acyrthosiphon pisum is elevated when aphids are reared on diets from which that EAA are omitted, demonstrating that Buchnera scale EAA production to host demand. Quantitative proteomics of bacteriocytes (host cells bear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
65
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 37 publications
0
65
0
Order By: Relevance
“…For example, 43 blood-feeding insects (such as tsetse flies, bedbugs and body lice) 44 have obligate bacterial symbionts that provide essential vitamins that 45 are absent from their blood meal diet [4][5][6][7]. Similarly, plant phloem- 46 feeding insects (such as aphids, psyllids, and mealybugs) have obligate 47 bacterial symbionts that provide essential amino acids and vitamins 48 that are absent or at low concentrations in their plant phloem sap diet 49 [4,[8][9][10]. 50 Currently, the best-characterized insect nutritional symbiosis is that of 51 the pea aphid, Acyrthosiphon pisum and its gammaproteobacterium 52 Buchnera aphidicola [11,12].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, 43 blood-feeding insects (such as tsetse flies, bedbugs and body lice) 44 have obligate bacterial symbionts that provide essential vitamins that 45 are absent from their blood meal diet [4][5][6][7]. Similarly, plant phloem- 46 feeding insects (such as aphids, psyllids, and mealybugs) have obligate 47 bacterial symbionts that provide essential amino acids and vitamins 48 that are absent or at low concentrations in their plant phloem sap diet 49 [4,[8][9][10]. 50 Currently, the best-characterized insect nutritional symbiosis is that of 51 the pea aphid, Acyrthosiphon pisum and its gammaproteobacterium 52 Buchnera aphidicola [11,12].…”
mentioning
confidence: 99%
“…S1) [14,19,20,22,45]. Regulation of precursor transport into host bacteriocyte cells and between symbiotic partners modulates amino acid biosynthetic output[17,47]. Previously, we demonstrated that glutamine transport by ApGLNT1 is inhibited by extracellular arginine; a Buchnera synthesized amino acid that can regulate pre-…”
mentioning
confidence: 99%
“…Metabolic models based on the presence and absence of amino acid biosynthesis genes in A. pisum and Buchnera, as well as amino acid uptake and labeling experiments, show that precursors for the biosynthesis of essential amino acids are transported from the aphid host to the bacterial endosymbionts (Brinza et al, 2010;Hansen and Moran, 2011;Poliakov et al, 2011;Russell et al, 2014;Sasaki and Ishikawa, 1995;Shigenobu et al, 2000;Wilson et al, 2010). Four amino acids, aspartic acid, asparagine, glutamic acid and glutamine, not only provide the majority of the nitrogen flow into the Buchnera endosymbionts for the synthesis of essential amino acids but also constitute the majority of the phloem amino acids in most plant species, including in V. faba, a natural host for A. pisum (Gündüz and Douglas, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…A clonal culture of the pea aphid (Acyrthosiphon pisum Harris) strain CWR09/18, derived from a single female collected in June 2009 from an alfalfa crop at Freeville Farms (Freeville, NY, USA) (Russell et al, 2014), was reared on faba beans (Vicia faba, var. Windsor; Johnny's Selected Seeds, Winslow, ME, USA), which were grown in Metromix 200 (Scotts, Marysville, OH, USA) in a growth chamber at 23°C and 100 µmol photons m −2 s −1 light intensity, with a 18 h:6 h light:dark cycle; 10 day old pre-flowering plants were used for aphid rearing.…”
Section: Aphid Rearingmentioning
confidence: 99%
“…Like all aphids, A. pisum feeds exclusively on plant phloem sap, a diet that is rich in sugar but limited in provision of essential amino acids and vitamins [35]. To overcome the nutritional deficiency of their diet, aphids anciently acquired B. aphidicola , an endosymbiont that metabolically compensates the nutritional shortcomings of their diet [1, 6, 7]. Buchnera is transmitted from generation to generation through transovarial transmission [8], and remarkably aphids cured of Buchnera infection fail to reproduce [912].…”
Section: Introductionmentioning
confidence: 99%